Low bone mineral density is related to atherosclerosis in postmenopausal Moroccan women - Cherkaoui Mohammed; Ichchou Linda; Mansouri Leila EL; Bennani Loubna; Khazzani Hamza; Allali Fadoua; Hmamouchi Ihsane; Abouqal Redouane; Hajjaj-Hassouni Najia (BMC, 2009)
Abstract Background Some studies have implicated several possible metabolic linkages between osteoporosis and vascular calcification, including estrogen deficiency, vitamin D excess, vitamin K deficiency and lipid oxidation products. Nevertheless, it remains unclear whether osteoporosis and atherosclerosis are related to each other or are independent processes, both related to aging. The aim of this cross-sectional study was to evaluate the correlation between arterial thickening and bone status in a sample of apparently healthy Moroccan women. Methods Seventy-two postmenopausal women were studied. All patients were without secondary causes that might affect bone density. Bone status was assessed by bone mineral density (BMD) in lumbar spine and all femoral sites. Arterial wall thickening was assessed by intima-media thickness (IMT) in carotid artery (CA) and femoral artery (FA). Prevalent plaques were categorized into four groups ranging from low echogenicity to high echogenicity. Results The mean age was 59.2 ± 8.3 years. 84.7% had at least one plaque. By Spearman Rank correlation, CA IMT was negatively correlated to Femoral total BMD (r = -0.33), Femoral neck BMD (r = -0.23), Ward triangle BMD (r = -0.30) and Trochanter BMD (r = -0.28) while there was no association with lumbar BMD. In multiple regression analysis, CA IMT emerged as an independent factor significantly associated with all femoral sites BMD after adjusting of confounding factors. FA IMT failed to be significantly associated with both Femoral and Lumbar BMD. No significant differences between echogenic, predominantly echogenic, predominantly echolucent and echolucent plaques groups were found concerning lumbar BMD and all femoral sites BMD Conclusion Our results demonstrate a negative correlation between bone mineral density (BMD) qnd carotid intima-media thickness (IMT) in postmenopausal women, independently of confounding factors. We suggest that bone status should be evaluated in patients with vascular disease to assess whether preventive or therapeutic intervention is necessarry.